Proposed Seed Pixel Region Growing Segmentation and Artificial Neural Network Classifier for Detecting the Renal Calculi in Ultrasound Images for Urologist Decisions - Sujata Navratnam; Siti Fazilah; Valliappan Raman; Sundresan A/L Perumal (Tech Science Publications, 2024)
Non-Indexed Publication